Teaching Spinal Cord Neuroanatomy through Drawing: An Interactive, Step-Wise Module - Katherine Gheysens; Robert Lebeau; Diana Glendinning (Association of American Medical Colleges, 2017)
Introduction This interactive, case-based module was created to provide medical students with self-guided practice to improve their confidence with, and understanding of, neuroanatomy. The module was created to supplement neuroanatomy instruction. It is based on the idea that pictures and drawings are effective tools for teaching clinical neuroanatomy, especially when paired with a step-wise approach to solving clinical cases. Methods The learning module focuses on the basics of spinal cord anatomy and lesion localization, topics fundamental to neuroanatomy. Students who have had a basic introduction to these topics in their neuroanatomy course will find this module a useful educational supplement. A full version of the module, which includes a self-drawing component for additional reinforcement, can be completed in approximately an hour. A shorter version without the self-drawing component, can be completed in less time. The materials associated with the module include an answer packet to use as a guide through the module cases, and both pre- and postmodule practice questions for self-evaluation. Both modules were tested at our institution by separate groups of second-year medical students in the early portion of their neuroanatomy course. Results Both module versions showed significant improvement in confidence levels when describing spinal cord anatomy and lesion localization. Furthermore, students were highly satisfied with the material and reported they were likely to reuse it for additional studying. Discussion The use of this module by medical students during their neuroanatomy course provides a step-wise, case-based approach that simplifies the learning of learning neuroanatomy, and improves their confidence through pictures and drawings.